Association of the Myosin-binding Subunit of Myosin Phosphatase and Moesin: Dual Regulation of Moesin Phosphorylation by Rho-associated Kinase and Myosin Phosphatase - Fukata, Yuko (The Rockefeller University Press, 1998)
The small GTPase Rho is believed to regulate the actin cytoskeleton and cell adhesion through its specific targets. We previously identified the Rho targets: protein kinase N, Rho-associated kinase (Rho- kinase), and the myosin-binding subunit (MBS) of myosin phosphatase. We found that in MDCK epithelial cells, MBS accumulated at the tetradecanoylphorbol-13-acetate (TPA)-induced membrane ruffling area, where moesin, a member of the ERM (ezrin, radixin, and moesin) family, was localized. Neither membrane ruffling nor an accumulation of moesin and MBS at the free-end plasma membrane was induced when MDCK cells were stimulated with TPA after the microinjection of C3, which ADP-ribosylates and inactivates Rho. MBS was colocalized with moesin at the cell–cell contact sites in MDCK cells. We also found that moesin was coimmunoprecipitated with MBS from MDCK cells. Recombinant MBS interacted with the amino-terminal domains of moesin and ezrin. Myosin phosphatase composed of the catalytic subunit and MBS showed phosphatase activity toward moesin, which was phosphorylated by Rho-kinase. The phosphatase activity was inhibited when MBS was phosphorylated by Rho-kinase. These results suggest that MBS is recruited with moesin to the plasma membrane and that myosin phosphatase and Rho-kinase regulate the phosphorylation state of moesin downstream of Rho.